Saunders comprehensive review for the NCLEX-PN examination - Silvestri, Linda Anne. (St. Louis, Mo. : Elsevier/Saunders, 2014)
This review and test preparation guide offers a combination of core content review, practice questions, comprehensive rationales, and detailed test-taking strategies. It contains more than 4,200 practice questions both in the text and on the companion Evolve site. Alternative item formats are provided, including multiple response, ordered response, fill-in-the-blank, figure, chart/exhibit, audio, graphic option, and video questions. Pharmacology chapters reflect the emphasis on medication and calculation questions. Priority nursing actions boxes outline and explain clinical emergent situations requiring immediate action to reinforce prioritizing skills in clinical and testing situations. The comprehensive test incorporates questions related to all content areas in the book and is representative of the percentages identified in the NCLEX-PN exam test plan. Strategies for taking the NCLEX-PN exam are also covered. Codes for client needs, content area, nursing process, level of cognitive ability, and integrated process are included with every review question.
The Adult Client With an Integumentary Disorder. Integumentary system ; Integumentary medications. -- The Adult Client With an Oncological Disorder. Oncological disorders ; Antineoplastic medications. -- The Adult Client With an Endocrine Disorder. Endocrine system ; Endocrine medications. -- The Adult Client with a gastrointestinal disorder : Gastrointestinal system ; Gastrointestinal medications. -- The Adult Client With a Respiratory Disorder. Respiratory system ; Respiratory medications. -- The Adult Client With a Cardiovascular Disorder. Cardiovascular disorders ; Cardiovascular medications. -- The Adult client with a Renal Disorder. Renal system ; Renal medications. -- The Adult Client With an Eye or Ear Disorder. The eye and the ear ; Ophthalmic and otic medications. -- The Adult Client With a Neurological Disorder. Neurological system ; Neurological medications. -- The Adult Client With a Musculoskeletal Disorder. Musculoskeletal system ; Musculoskeletal medications. -- The Adult Client With an Immune Disorder. Immune disorders ; Immunological medications. -- The Adult Client With a Mental Health Disorder. Foundations of psychiatric mental health nursing ; Mental health disorders ; Addictions ; Crisis theory and intervention ; Psychiatric medications. -- Comprehensive Test.
Includes bibliographical references and index.
Keywords: Practical nursing -- Examinations, questions, etc; National Council Licensure Examination for Practical/Vocational Nurses -- Study guides; Nursing, Practical -- Examination Questions; Nursing Care -- Examination Questions